Bioactive Heterocycles: Green Synthesis and its Anti-Alzheimer Activity - Fathima Afridha, Mohamed S. H.; Aazath, Kathar; Roopan, Selvaraj M.; Anto Simplica, Sagayaraj Jane (Current Green Chemistry, 2023)
The wide pharmaceutical activity of the bioactive heterocycles, which include nitrogen, oxygen, and sulphur and comprise five- and six-membered rings, has drawn the attention of medicinal chemists for several years. The therapeutic potential of bioactive heterocycles for a variety of disorders lies in their medicinal effects. The most prominent of them is Alzheimer's disease (AD), a neurodegenerative disorder that impairs memory and causes other psychiatric problems. Globally, there are around 54 million cases, and by 2050, that number is predicted to rise by 131 million. So far, donepezil, galantamine, and rivastigmine have indeed received FDA approval for use in the treatment of AD. In this regard, the pharmacophoric properties of heterocycle molecules are equivalent to those of galantamine mimics. Therefore, it is beneficial to create novel compounds containing these moieties and test their ability to inhibit acetyl and butyl cholinesterase. Diverse heterocyclic scaffolds may now have therapeutic potential for Alzheimer's disease. Recently, greener and more expeditious synthesis of bioactive heterocycles has drawn much attention because of the utilisation of environmentally benign protocols, thereby diminishing the usage of hazardous chemicals. In this review, we discuss the most pertinent findings about the
Keywords: Alzheimer’s disease